New Labour’s Grassroots - Seyd, P. author. aut Link
XXII, 206 p. 8 illus.
Keywords: Based on a unique series of surveys conducted during the 1990s, this book examines changes in the social backgrounds, attitudes, beliefs and political activities of Labour party members. It addresses questions such as: What do Labour party members think of New Labour and its policies? How important are the members to the party? Are they becoming more or less active over time? Can the party dispense with its membership and still remain viable?